Diversion as a Form of Settlement of Child Criminal Cases Through the Restorative Justice System by Investigators - Hetharie, Mesakh Yohanes; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Cases of violence between children often occur, this is because the emotional maturity of children is not yet fully mature so that pathological social problems often occur which make children often commit violence between each other. This makes children often face the law, therefore children need a guarantee of mental protection and intellectual growth, so the concept of restorative justice through diversion is needed, however, diversion has not been optimally implemented, especially in the Cirebon City area. This study aims to describe the process of investigation of child criminal cases through restorative justice at the Cirebon City Police. To analyze the obstacles and solutions in the process of investigation of child criminal cases through restorative justice at the Cirebon City Police. The type of research used in this study is a descriptive analytical legal research type. Based on the research results, it is known that the investigation process for child criminal cases through diversion as an effort to realize restorative justice at the Cirebon City Police is not yet optimal, this is because 95 cases of violence committed by children were resolved at the Cirebon City District Court in 2024.Constraintin the process of investigating cases of child criminal acts through restorative justice at the Cirebon City Police in the form of the lack of public knowledge regarding the resolution of criminal cases through restorative justice; the lack of public awareness to reconcile through restorative justice in cases of minor assault; and the lack of regulation of the resolution of hate speech crimes through restorative justice in a complete and specific manner at the level of government regulations, both central and regional.